Studi Pemahaman Aturan Etika dalam Kode Etik Akuntan: Simulasian Etika Pengauditan - -, Rustiana (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2009)
This Ã‚Â paper Ã‚Â is Ã‚Â to Ã‚Â investigate Ã‚Â ability Ã‚Â of Ã‚Â accounting Ã‚Â student Ã‚Â about Ã‚Â code Ã‚Â of conduct Ã‚Â accountingÃ‚Â ethics. The definition of ethics is the philosophical study of morality, and, accordingly, morality isÃ‚Â clearly identified as the characteristic subject matter of ethic. We use ten scenarios concerningÃ‚Â ethical dilemmas in auditing. Data was drawn from a sample of 78 accounting students enrolledÃ‚Â in accounting seminar and auditing 2 of Atma Jaya Yogyakarta University. Data collection methodÃ‚Â is used by a personally questionnaires survey. Data were analysed by qualitative technique. TheÃ‚Â results show that accounting students have good ability to learn about ethical dilemmas in auditing.Ã‚Â The implications of the study are to increasing content of ethic in accounting curricula.